The Role of local ombudsman committee in promoting good governance : a case study of the local public ombudsman in Yogyakarta, Indonesia - Tarmedi, Fransiskus Adrian (Chulalongkorn University, 2013)
Thesis (M.A.)--Chulalongkorn University, 2012